Laser Application for Management of Traumatic Ulcers Following Local Anesthesia in Children - Tanya Agarwal; Needhika Registrar; Sania; Pranav Gupta; Deepak Kurup; Srishti (Indian Journal of Forensic Medicine & Toxicology, 2022)
Prolonged local anaesthesia in soft perioral tissues may sometimes lead to accidental lip biting in small children forming a traumatic ulcer. Healing of such ulcers has been reported to enhance with treatment using low level laser therapy (LLLT). This case report describe two cases of traumatic ulcers due to lip bite following inferior alveolar nerve block caused during post anaesthesia period that were treated by LLLT. It resulted in better healing and lower pain, thus helping in healing and repair of the tissue.